Experimental investigation and numerical prediction of static strength and fracture behaviour of notched epoxy-based structural adhesives. (September 2019) - Beber, V.C.; Schneider, B.; Brede, M.
Abstract: The influence of stress concentrations on the tensile static strength and fracture behaviour of notched bulk specimens was investigated by comparing the response of two epoxy-based structural adhesives (a rubber-toughened and a polyurethane-toughened). Numerical predictions of failure stress were carried out using a 3D-FEA model with a hydrostatic dependent elastoplastic material behaviour and the equivalent plastic strain for failure assessment. The ductile adhesive, which plastically deforms more under high stresses, provided experimental evidence of a notch strengthening effect. Conversely, the less ductile adhesive has shown a reduction in tensile strength compared to un-notched samples. For both adhesives fracture surface analysis showed the presence of stress whitening and voids close to the notch regions. These regions could be correlated to higher values of stress triaxiality using numerical simulation. The more ductile adhesive underwent widespread stress whitening prior to failure, whereas the response of the less ductile adhesive was more localised. Numerically based predictions showed excellent agreement with experimental results with average error of 5.1% for different notch types in both adhesives.